2009
DOI: 10.1113/jphysiol.2009.177881
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of GLT‐1 severely impairs LTD at mossy fibre–CA3 synapses

Abstract: Glutamate transporters are responsible for clearing synaptically released glutamate from the extracellular space. By this action, they maintain low levels of ambient glutamate, thus preventing excitotoxic damage, and contribute to shaping synaptic currents. We show that up-regulation of the glutamate transporter GLT-1 by ceftriaxone severely impaired mGluR-dependent long-term depression (LTD), induced at rat mossy fibre (MF)-CA3 synapses by repetitive stimulation of afferent fibres. This effect involved GLT-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 49 publications
(68 reference statements)
4
113
1
2
Order By: Relevance
“…Rothstein et al (2005) showed that CEF robustly stimulates GLT-1 expression, but not that of the other glutamate transporters, through increased GLT-1 gene transcription. This finding has been replicated in different laboratories (eg, Chu et al, 2007;Ouyang et al, 2007;Lee et al, 2008), including ours Omrani et al, 2009). We also showed that CEF increases GLT-1a expression in forebrain regions that regulate PPI of the startle .…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Rothstein et al (2005) showed that CEF robustly stimulates GLT-1 expression, but not that of the other glutamate transporters, through increased GLT-1 gene transcription. This finding has been replicated in different laboratories (eg, Chu et al, 2007;Ouyang et al, 2007;Lee et al, 2008), including ours Omrani et al, 2009). We also showed that CEF increases GLT-1a expression in forebrain regions that regulate PPI of the startle .…”
Section: Discussionsupporting
confidence: 70%
“…mGluR2/3 activation depends on the spread of glutamate from release sites to the perisynaptic zone, where these receptors are predominantly located (Scanziani et al, 1997;Min et al, 1998;Mitchell and Silver, 2000;Ferraguti and Shigemoto, 2006); and GLT-1 controls extracellular levels of glutamate and it is mainly localized perisynaptically (Melone et al, 2009a). Thus, by modulating glutamate spillover, GLT-1 influences activation of mGluR2/3 Barbour, 2001;Diamond, 2002;Tzingounis and Wadiche, 2007;Zheng et al, 2008;Omrani et al, 2009). Our western blotting and immunocytochemical studies are consistent with this view.…”
Section: Ly379268 Blocks Cef-induced Ppi Impairment M Bellesi and F Csupporting
confidence: 78%
See 3 more Smart Citations